Fiqih Lingkungan dan Ekologi Islam - Zainal Abidin; Syachyun Mahisa Sembiring; Lenni Khairani; Herwin Herwin (LP2M Universitas Islam Ahmad Dahlan, 2026)
This study aims to examine the concept of Environmental Fiqh in Islam and its relevance in addressing contemporary ecological issues. Using a qualitative approach based on library research, this study analyzes primary sources from the Qur’an, hadith, and the literature of classical and contemporary scholars. The results of the study reveal four specific key findings: (1) Environmental Fiqh is structurally grounded in three main principles derived from the Qur’an and hadith, namely balance (mīzān) as stated in S. al-Raḥmān: 7–9, the prohibition against causing corruption (fasād) in Quran 2:11–12, and the obligation to be frugal and avoid wastefulness (isrāf and tabẓīr); (2) the concept of human stewardship (Quran 2:30) establishing binding ecological responsibilities, wherein environmental destruction is categorized as a betrayal of the divine trust; (3) Environmental Fiqh directly supports the five objectives of Maqāṣid al-Syarī‘ah the preservation of religion, life, intellect, lineage, and property since environmental degradation has been proven to threaten every aspect of these public interests; and (4) Islamic ecological principles, particularly intergenerational justice and ecosystem balance, align with the United Nations’ Sustainable Development Goals (SDGs), thereby enabling Environmental Fiqh to serve as Islam’s normative contribution to the global ecological discourse. These findings indicate that Environmental Fiqh constitutes a comprehensive Islamic legal framework that can be operationalized in addressing contemporary ecological crises.